Estimating productivity growth of Spanish ports using a non-radial, non-oriented Malmquist index. (3rd August 2009) - Lozano, Sebastian
Total factor productivity is commonly measured through the Malmquist productivity index (MPI). The original MPI is computed either with input or output orientation and using a radial efficiency measure. Several non-radial MPI and non-oriented variants have also been proposed. In this paper we use a non-radial, non-oriented MPI to estimate productivity growth of Spanish Ports. This has the advantage of taking into account efficiency improvements in all input and output dimensions. Technical efficiency change, technological change and scale efficiency changes are also derived following Ray and Desli (1997) decomposition. Computed productivity growth estimations are compared with the conventional radial, output oriented MPI as with the proportional distance-based Malmquist Luenberger productivity indicator.